The Effect of Profitability, Liquidity, Solvency, and Activity Ratios on Stock Prices with Dividend Payout Ratio as A Moderation Variable in Insurance Companies in Indonesia - Apriani Simatupang; Aura Juliana Sirait; Radityo Arianto (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study aims to examine the influence of proxied financial performance on profitability, liquidity, solvency, and activity ratios, which are then moderated by dividend policy on the share price of insurance companies in Indonesia. Multi-linear regression panel data with a random effect approach was used to investigate the factors that influence stock prices. The sample data was selected to be limited to insurance companies listed on the Indonesia Stock Exchange (IDX) from 2014 to 2023. The data tested included 12 insurance companies listed on the Indonesia Stock Exchange (IDX). The data was obtained from the company's quarterly report which can be accessed through S&P Capital IQ. In this study, the software used to process the data is Stata version 17. The results show that the profitability ratio proxied at Return on Equity (ROE), solvency ratio proxied at Debt to Equity Ratio (DER), activity ratio proxied at Total Assets Turnover (TATO), and dividend policy proxied at Dividend Payout Ratio (DPR) have a significant effect on stock prices. Meanwhile, the ratio of liquidity proxied to the Current Ratio (CR) has no significant effect on the stock price and the DPR cannot moderate the influence of ROE on the stock price.